A HISTORICAL LOOK AT THE MODERN PRINCIPLES AND PRACTICE OF REAL ESTATE OF DEVELOPMENT (American Journal of Business Management, Economics and Banking, 2023)
The review of the article presents the chronological history of modern development. This serves as a background against which the development of models for estimating the real value of development can be traced.